1999
DOI: 10.1121/1.425642
|View full text |Cite
|
Sign up to set email alerts
|

Considerations for including surface scattering in room-acoustics auralization

Abstract: Recent research in auralization has centered on including wave-theoretical aspects that are unaccounted for by well-developed but frequency-limited geometrical models [Dalenbäck et al., J. Audio Eng. Soc. 42(10) (1994)]. For example, inclusion of edge diffraction (or edge scattering) has been shown (via scale-model measurements and listening tests) to contribute audibly to the early part of the room impulse response [Torres and Kleiner, Proc. 16th Intl. Congress on Acoust. (1998)]. Modeling room surface scatte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…On the other hand, as demonstrated by the picture above, the new formulation produces realistic impulse responses, where also the first-order reflections are always followed by a diffuse tail. as it always happen with measured impulse responses [11].…”
Section: Diffuse Reflectionsmentioning
confidence: 60%
“…On the other hand, as demonstrated by the picture above, the new formulation produces realistic impulse responses, where also the first-order reflections are always followed by a diffuse tail. as it always happen with measured impulse responses [11].…”
Section: Diffuse Reflectionsmentioning
confidence: 60%
“…diffusion not varied below the 125 Hz octave but previous studies on including edge-diffraction in auralization [2] have shown that addition of edge-diffraction is audible in this range. Future subjective tests should also employ more accurate scattering models like those discussed in [4] Or perhaps higher-order diffusion models [11].…”
Section: Future Workmentioning
confidence: 99%
“…and auralization of various types of surface scattering via scale-model measurements [1][2][3]. This paper stems from a presentation of potential scattering models for room auralization [4] and discusses the subjective tests in detail. What kinds of approximations can be made to complex scattering models, while still retaining accurate auralization?…”
Section: Introductionmentioning
confidence: 99%